Screening of Biomarkers and Toxicity Mechanisms of Rifampicin-Induced Liver Injury Based on Targeted Bile Acid Metabolomics - Deng, Yang; Luo, Xilin; Li, Xin; Xiao, Yisha; Xu, Bing; Tong, Huan (Frontiers in Pharmacology, 2022)
Rifampicin (RIF) is a critical first-line drug for tuberculosis. However, long-term or high-dose treatment with RIF can induce severe liver injury; the underlying mechanism of this effect has not yet been clarified. This study was performed to screen reliable and sensitive biomarkers in serum bile acids (BAs) using targeted BA metabolomics and evaluate the toxicity mechanisms underlying RIF-induced liver injury through the farnesoid x receptor (Fxr)-multidrug resistance-associated proteins (Mrps) signaling pathway. Thirty-two Institute of Cancer Research mice were randomly divided into four groups, and normal saline, isoniazid 75 mg/kg + RIF 177 mg/kg (RIF-L), RIF-L, or RIF 442.5 mg/kg (RIF-H) was orally administered by gavage for 21 days. After treatment, changes in serum biochemical parameters, hepatic pathological conditions, BA levels, Fxr expression, and BA transporter levels were measured. RIF caused notable liver injury and increased serum cholic acid (CA) levels. Decline in the serum secondary BAs (deoxycholic acid, lithocholic acid, taurodeoxycholic acid, and tauroursodeoxycholic acid) levels led to liver injury in mice. Serum BAs were subjected to metabolomic assessment using partial least squares discriminant and receiver operating characteristic curve analyses. CA, DCA, LCA, TDCA, and TUDCA are potential biomarkers for early detection of RIF-induced liver injury. Furthermore, RIF-H reduced hepatic BA levels and elevated serum BA levels by suppressing the expression of Fxr and Mrp2 messenger ribonucleic acid (mRNA) while inducing that of Mrp3 and Mrp4 mRNAs. These findings provide evidence for screening additional biomarkers based on targeted BA metabolomics and provide further insights into the pathogenesis of RIF-induced liver injury.